Bussiness Course: Aplikasi Pembelajaran Kewirausahaan Berbasis Simulasi Studi Kasus dan Pengambilan Keputusan untuk Siswa dan Mahasiswa - Nailariza Umami; Heri Pratikto; Agus Hermawan (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
Strengthening entrepreneurship education at the high school (SMA/SMK) and university levels requires an approach that integrates theory with real-world practice. However, many students still struggle to fully understand business strategies due to limited hands-on experience and a lack of access to contextual business simulations. This study aims to develop a prototype of a learning application for entrepreneurship education called Business Course, which is based on case study simulations and decision-making scenarios. The application is designed to help users understand the dynamics of the business world through simple virtual scenarios that reflect real challenges in various types of enterprises, such as trade, services, culinary, and agriculture. The research method used is Research and Development (R&D) with the ADDIE model, and the development has currently reached the prototyping phase using Figma. Initial results indicate that the design of features and simulation flow allows users to identify problems, choose alternative solutions, and evaluate their impacts on business performance in a virtual setting. This application is expected to serve as an alternative, practical, and contextual learning medium that supports learning outcomes in entrepreneurship curricula. The research will continue with a testing phase to measure the effectiveness of the application in improving entrepreneurial competencies